2018
DOI: 10.1093/mnras/sty2011
|View full text |Cite
|
Sign up to set email alerts
|

A new algorithm to quantify maximum discs in galaxies

Abstract: Maximum disc decompositions of rotation curves place a dynamical upper limit to the mass attributable to stars in galaxies. The precise definition of this term, however, can be vague and varies in usage. We develop an algorithm to robustly quantify maximum-disc mass models and apply it to 153 galaxies from the SPARC database. Our automatic procedure recovers classic results from manual decompositions. Highmass, high-surface-brightness galaxies have mean maximum-disc mass-to-light ratios of ∼ 0.7 M /L in the Sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Neglecting measurements with large uncertainties, ∼ 90% of the bars are consistent with the fast regime at 95% confident level. These galaxies should host little DM in their central regions, in agreement with the findings based on the study of rotation curves for unbarred galaxies (Debattista & Sellwood 2000;Starkman et al 2018).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Neglecting measurements with large uncertainties, ∼ 90% of the bars are consistent with the fast regime at 95% confident level. These galaxies should host little DM in their central regions, in agreement with the findings based on the study of rotation curves for unbarred galaxies (Debattista & Sellwood 2000;Starkman et al 2018).…”
Section: Introductionsupporting
confidence: 88%
“…The slow down of the bar is stronger if a massive and centrally-concentrated DM halo is present, because there is more mass ready to absorb angular momentum near the resonances and dynamical friction is more efficient (see Athanassoula 2014 andSellwood 2014, for further discussion). This implies that galaxies hosting fast bars should be embedded in DM halos with a low central density, such as those required in the maximum disc hypothesis (Debattista & Sellwood 2000;Palunas & Williams 2000;Fuchs 2001;Starkman et al 2018). Nevertheless, other galaxy properties may influence the angular momentum exchange within the galaxy, such as the halo triaxiality, presence of gas, and disc velocity dispersion (Athanassoula 2003;Athanassoula et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In our computation, we fix the total gas mass to match the total mass inferred from the photometry and vary the stellar mass-to-light ratio of the disk from ϒ d ¼ 0 up to larger values that saturate the observed kinematic velocity [61]. In Fig.…”
Section: Application: Low-surface Brightness Sparc Galaxiesmentioning
confidence: 99%
“…( 1)). Here we adjust their values to achieve a maximum-disk fit (van Albada & Sancisi 1986;Starkman et al 2018), ensuring that the inner part of the observed rotation curve is fully explained by luminous matter. Our fits can be seen in Fig.…”
Section: Maximum-disk Mass Modelsmentioning
confidence: 99%